Biochemical investigation of a human pathogenic mutation in the nuclear ATP5E gene using yeast as a model - Sardin, Elodie; Donadello, Stéphanie; di Rago, Jean-Paul; Tetaud, Emmanuel (Frontiers in Genetics, 2015)
F1F0-ATP synthase is a key enzyme of the mitochondrial energetic metabolism responsible for the production of most cellular ATP in humans. Mayr et al. (Mayr JA, Havlickova V, Zimmermann F, Magler I, Kaplanova V, Jesina P, Pecinova A, Nuskova H, Koch J, Sperl W and Houstek J. 2010. Hum Mol Genet) recently described a patient with a homozygote (Y12C) mutation in the nuclear gene ATP5E encoding the ε-subunit of ATP synthase. To better define how it affects ATP synthase, we have modelled this mutation in the yeast Saccharomyces cerevisiae. A yeast equivalent of this mutation (Y11C) had no significant effect on the growth of yeast on non-fermentable carbon sources (glycerol/ethanol or lactate), conditions under which the activity of the mitochondrial energy transducing system is absolutely essential. In addition, similar to what was observed in patient, this mutation in yeast has a minimal effect on the ATPase/synthase activities. On the contrary, this mutation which has been shown to have a strong impact on the assembly of the ATP synthase complex in humans, shows no significant impact on the assembly/stability of this complex in yeast, suggesting that biogenesis of this complex differs significantly.